Vaccine effectiveness of recombinant and standard dose influenza vaccines against outpatient illness during 2018-2019 and 2019-2020 calculated using a retrospective test-negative design - Richard K. Zimmerman; Klancie Dauer; Lloyd Clarke; Mary Patricia Nowalk; Jonathan M. Raviotta; G. K. Balasubramani (Taylor & Francis Group, 2023)
Newer influenza vaccine formulations have entered the market, but real-world effectiveness studies are not widely conducted until there is sufficient uptake. We conducted a retrospective test-negative case-control study to determine relative vaccine effectiveness (rVE) of recombinant influenza vaccine or RIV4, compared with standard dose vaccines (SD) in a health system with significant RIV4 uptake. Using the electronic medical record (EMR) and the Pennsylvania state immunization registry to confirm influenza vaccination, VE against outpatient medically attended visits was calculated. Immunocompetent outpatients ages 18-64 years seen in hospital-based clinics or emergency departments who were tested for influenza using reverse transcription polymerase chain reaction (RT-PCR) assays during the 2018-2019 and 2019-2020 influenza seasons were included. Propensity scores with inverse probability weighting were used to adjust for potential confounders and determine rVE. Among this mostly white and female cohort of 5,515 individuals, 510 were vaccinated with RIV4 and 557 were vaccinated with SD, with the balance of 4,448 (81%) being unvaccinated. Adjusted influenza VE estimates were 37% overall (95% CI = 27, 46), 40% (95% CI = 25, 51) for RIV4 and 35% (95% CI = 20, 47) for standard dose vaccines. Overall, rVE of RIV4 compared to SD was not significantly higher (11%; 95% CI = −20, 33). Influenza vaccines were moderately protective against medically attended outpatient influenza during the 2018-2019 and 2019-2020 seasons. Although the point estimates are higher for RIV4, the large confidence intervals around VE estimates suggest this study was underpowered to detect significant rVE of individual vaccine formulations.